THU0139 Methotrexate Use and Liver Disease in Rheumatoid Arthritis: A Meta-Analysis of Randomised Controlled Trials. (10th June 2014) - Conway, R.; Low, C.; Coughlan, R.J.; O'Donnell, M.J.; Carey, J.J.
Abstract : Background: Methotrexate is the most widely prescribed DMARD in the treatment of rheumatoid arthritis. Recent multinational evidence-based recommendations advise the cessation of methotrexate if transaminases are persistently greater than three times the upper limit of normal (>3 ULN). Our understanding of the relative risk of liver function test abnormalities with methotrexate and the significance of these remains incomplete and may be influenced by reporting bias. Objectives: To evaluate the relative risk, severity and significance of liver function test abnormalities in patients with rheumatoid arthritis prescribed methotrexate in double-blind randomised controlled trials. Methods: We performed a systematic literature search of Pubmed and Cochrane databases from 1st January 1990 to 1st November 2013 for double-blind randomised controlled trials of methotrexate versus placebo or active comparator agents in adults with rheumatoid arthritis. Studies with less than 100 subjects, of less than 24 weeks duration, or with no reporting of liver adverse events were excluded. Two investigators independently searched both databases. All authors reviewed selected studies. Random effects meta-analysis using the Mantel-Haenszel method was used to assess total liver events, minor liver adverse events (≤3 ULN), major liver adverse events (>3 ULN or treatment withdrawal) and a composite outcome of liver failure, cirrhosis, or death. Results were expressed as relative risks (RR) with 95% confidence intervals. Results: A total of 27 studies with 11485 participants met our inclusion criteria. Methotrexate was associated with an increased risk of all adverse liver events, RR 2.15 (95% CI 1.64-2.81), as well as minor and major liver function test abnormalities, RR 2.07 (95% CI 1.56-2.75) and RR 2.87 (95% CI 1.87-4.39) respectively. Patients treated with methotrexate were not at increased risk of liver failure, cirrhosis or death, RR 0.12 (95% CI 0.01-1.09). Conclusions: Our study found an increased risk of elevated transaminases detected on monitoring blood tests in rheumatoid arthritis patients treated with methotrexate compared to other disease-modifying antirheumatic drugs and biologic agents. This did not translate into an increased risk of liver failure, cirrhosis, or death. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.1799